Exploring the mechanism of Heidihuang Pill in the treatment of osteoporosis based on network pharmacology, molecular docking, and experimental validation - Tian, Zenghui; Cui, Kaiying; Tian, Yuxiao; Chen, Yungang; Liu, Guoyan; Zhang, Farong; Hao, Yanke; Li, Yingying (Frontiers in Endocrinology, 2025)
BackgroundCurrently, anti-osteoporosis (OP) treatment imposes a certain economic burden on patients and society; therefore, studies have focused on exploring anti-OP therapies. As a classic prescription in traditional Chinese medicine (TCM), the Heidihuang Pill (HP) was clinically shown to alleviate OP. However, the mechanism behind its effect remains unclear. We aimed to determine this mechanism using methods such as network pharmacology and experimental verification.MethodsNetwork pharmacology was used to identify the active ingredients, targets, and mechanisms of action of HP in treating OP. Molecular docking technology was then used to verify the interactions between the active ingredients and target proteins. Finally, an OP rat model was established through in vivo experiments to validate the results obtained from network pharmacology.ResultsOverall, 178 targets were retrieved, which are key targets of HP for treating OP. Protein-Protein Interaction network analysis showed that RAC-alpha serine/threonine-protein kinase (Akt1) (degree =132) was the most reliable target of HP for treating OP. Gene Ontology functional analysis revealed that the regulation of HP on OP mainly occurs as follows: it mainly manifests as a response to hormones in biological processes; it mainly acts on membrane rafts in cellular components; and it mainly involves the binding of transcription factors in molecular functions. Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis indicated that the Advanced Glycation End products/Receptor for Advanced Glycation End products (AGE-RAGE) signaling pathway in diabetic complications and the hypoxia-inducible factor (HIF)-1 signaling pathway are the main pathways involved in the HP treatment of OP. Molecular docking results showed that Akt1 has a good binding ability with peoniflorin, with a binding energy of -56.66 kcal/mol. In vivo experiments confirmed that the trabecular bone mineral density, trabecular number, and bone volume fraction of model rats treated with HP significantly increased (P < 0.05 vs. the model group). Histopathological staining showed that the number and morphology of the trabecular bones improved (vs. the model group). Additionally, the expression of HIF-1 signaling protein in rat bone tissue increased, while the expression of AGE/RAGE signaling protein decreased (P < 0.05, vs. the model group).ConclusionPeoniflorin, the main active ingredient in HP, acts on Akt1 and treats OP through the AGE-RAGE and HIF-1 signaling pathways. This study showed the precise molecular pathways and core therapeutic targets of HP in treating OP, and provides a scientific basis and new research direction for treating OP with TCM.